Sinodāli Episkopālā Iekārta Latvijas Evaņģēliski Luteriskajā Baznīcā Laikposmā No 1931. Līdz 1940. Gadam: Synodal Episcopal order in the Latvian Evangelical Lutheran Church 1931-1940. - Rozentāls, Linards (Cel̜š, 2012)
In 1931 the Bishop of the Evangelical Lutheran Church of Latvia K. Irbe suggested discussions at the deaneries about various topics of the planned Synod at the end of 1931, and also about the shortcomings of the episcopal synodal order or demand its substitution with the episcopal order. As this suggestion was not supported by the deaneries and was not included in the agenda of the Synod, the theme of the change in church order initiated by Bishop K. Irbe was concluded in 1932 by the decree of the Consistory that "the synodal episcopal order is not to be changed." However, in practice, during the period between 1934 and 1940, as a result of the initiative of the church itself and of the autoritarian state administration, the synodal episcopal order was de facto replaced by the episcopal order and all the prerequisites - the draft law about the state church and the new church Constitution - for introducing the state church model created in 1940. These processes formed the understanding of the church and its relations with the state that substantially enabled the Soviet authorities to implement the policy of sovietisation of the Latvian Evangelical Lutheran church and bringing it under Soviet interests, depriving the church of its rights of autonomy and self-determination. While the intention of the autoritarian regime was to integrate the church into the structures of state power and administration, the aim of the Soviet regime was to weaken the church as an institution as much as possible and to consign it to oblivion and extinction.